Backstepping Method for Stabilizing System of 2×2 Riccati Matrix Differential Equations - H. Shather, Akram (Al-Nahrain Journal of Science, 2020)
In this research paper, the backstepping method (BSM) will be proposed for stabilizing and solving system of 2×2 Riccati matrix ordinary differential equations. Such equations have many difficulties in the studying their solutions and stability. The basic idea behind of this approach is to use the BSM as a transformation method for transforming the original system into an equivalent one which is stabilizable and solvable based on constructing the Lyapunov function.